Expression of the Ets transcription factors erm and pea3 in early zebrafish development - Münchberg, Susanne R; Ober, Elke A.; Steinbeisser, Herbert (Mechanisms of Development, 1999)
Here we report the cloning of zebrafish erm and pea3 cDNAs, which are members of the PEA3 subgroup of Ets transcription factors. The expression patterns of these two genes were examined during zebrafish embryogenesis. Maternal mRNAs of both genes are detectable and transcripts are found ubiquitously until the late blastula, in the marginal zone of gastrula stages and in the presumptive fore- and hindbrain and in the trunk region of early somite stages. Later, erm expression is observed in distinct regions of the forebrain, the mid-/hindbrain boundary, the differentiating rhombomeres, branchial arches, otic vesicles, the pectoral fins, the somites and the tailbud in a dynamic fashion. In contrast, pea3 is not expressed in the rhombomeres but in the Rohon–Beard neurons, the sensory lateral line placodes and the heart.<br
Keywords: Ets transcription factors; erm; pea3; Zebrafish; Embryogenesis